2022
DOI: 10.3389/fpls.2022.1087839
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of sucrose non-fermenting-1-related protein kinase genes in maize and their responses to abiotic stresses

Abstract: IntroductionProtein kinases play an important role in plants in response to environmental changes through signal transduction. As a large family of protein kinases, sucrose non-fermenting-1 (SNF1)-related kinases (SnRKs) were found and functionally verified in many plants. Nevertheless, little is known about the SnRK family of Zea mays.MethodsEvolutionary relationships, chromosome locations, gene structures, conserved motifs, and cis-elements in promoter regions were systematically analyzed. Besides, tissue-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…We found that ZmCKX1 0 ( Zm00001eb040280 ) encoding cytokinin dehydrogenase and an auxin‐responsive gene, ZmIAA20 ( Zm00001eb213730 ) were located in 195–213.2 Mb and 4.4–39.3 Mb hotspots on chromosomes 1 and 5, respectively (Figure 3e; Table S9). Besides, ZmCIPK44 ( Zm00001eb163480 ) was reported to respond to abiotic stresses via an ABA‐dependent pathway (Feng et al., 2022). Therefore, these phytohormones‐related genes may play important roles in response to N stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that ZmCKX1 0 ( Zm00001eb040280 ) encoding cytokinin dehydrogenase and an auxin‐responsive gene, ZmIAA20 ( Zm00001eb213730 ) were located in 195–213.2 Mb and 4.4–39.3 Mb hotspots on chromosomes 1 and 5, respectively (Figure 3e; Table S9). Besides, ZmCIPK44 ( Zm00001eb163480 ) was reported to respond to abiotic stresses via an ABA‐dependent pathway (Feng et al., 2022). Therefore, these phytohormones‐related genes may play important roles in response to N stress.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, ZmCIPK44 (Zm00001eb163480) was reported to respond to abiotic stresses via an ABA-dependent pathway (Feng et al, 2022). Therefore, these phytohormones-related genes may play important roles in response to N stress.…”
Section: Identification Of Candidate Genes For Nue Improvement By Int...mentioning
confidence: 99%
“…The second gene, Zm00001d015765, is an ortholog of Arabidopsis AtSWC4, which suppresses the expression of FT (florigen) and accelerates flowering time when knocked down (Gómez-Zambrano et al, 2018). Additionally, three outlier SNPs were found within genes whose expression is modified under stress conditions (Supplementary table 8A): the gene Zm00001d020497, identified as cipk28 (calcineurin B-like-interacting protein kinase28), has been observed to exhibit responses to both salt and drought stresses (Chen et al, 2013; Feng et al, 2022). Similarly, Zm00001d047587 encodes a glucose-6-phosphate dehydrogenase (G6PDH3) and has demonstrated induction under osmotic and cold stress (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%